Gender Diversity on Boards of Directors and Remuneration Committees: The Influence on Listed Companies in Spain - García-Izquierdo, Antonio L.; Fernández-Méndez, Carlos; Arrondo-García, Rubén (Frontiers in Psychology, 2018)
Women have traditionally been underrepresented on boards of companies, but after some social and legal pressure, their presence has been increased during recent years. This paper examines the relation of the presence of female directors both at board meetings and at audit and remuneration committees, with CEO pay and the shareholders’ consultative vote on managerial remuneration plans (“say on pay”). Using a large sample of Spanish firms listed between 2011 and 2015, our study reveals that firms with female representation on their remuneration committee, display lower levels of CEO pay and CEO pay growth. We also obtain evidence that this effect is attributable to the proprietary female directors. Additionally, from the ‘say on pay’ perspective, female membership of the remuneration committee is associated with a lower number of votes in terms of director remuneration reports and related policies. Overall, our results indicate that female directors on the remuneration committee contribute to a moderation of executive remuneration growth and are consequently perceived by shareholders as valuable resources in the design of executive remuneration plans. This confirms the influence of the minority group, females, in the sustainable progress of these companies. Our results support the presence of female directors not only as a social measure or tokenism, but also as a contribution to good governance practice.